Traumatic insemination and sexual conflict in the bed bug Cimex lectularius - Stutt, Alastair D. (The National Academy of Sciences, 2001)
The bed bug, Cimex lectularius, has a unique mode of copulation termed “traumatic” insemination [Carayon, J. (1966) in Monograph of the Cimicidae, ed. Usinger, R. (Entomol. Soc. Am., Philadelphia), pp. 81–167] during which the male pierces the female's abdominal wall with his external genitalia and inseminates into her body cavity [Carayon, J. (1966) in Monograph of the Cimicidae, ed. Usinger, R. (Entomol. Soc. Am., Philadelphia), pp. 81–167]. Under controlled natural conditions, traumatic insemination was frequent and temporally restricted. We show for the first time, to our knowledge, that traumatic insemination results in (i) last-male sperm precedence, (ii) suboptimal remating frequencies for the maintenance of female fertility, and (iii) reduced longevity and reproductive success in females. Experimental females did not receive indirect benefits from multiple mating. We conclude that traumatic insemination is probably a coercive male copulatory strategy that results in a sexual conflict of interests.